Legal framework for management of waqf land in Malaysia - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (LexisNexis, 2014)
The article discusses waqf land administration and the legal framework for waqf management at state level. It also describes the differences between waqf and trust and examines the position of waqf lands under the National Land Code 1965. Towards the end it identifies legal challenges in the management of waqf lands and concludes with recommendations and conclusions.